Selective synthesis of CuNi alloys using waste PCB and NiMH battery. (15th March 2019) - Farzana, Rifat; Hassan, Kamrul; Wang, Wei; Sahajwalla, Veena
Abstract: The aim of this study is to establish the potential novel approach for the selective synthesis of copper-nickel (CuNi) alloys using two waste streams, printed circuit board (PCB) and nickel-metal hydride (NiMH) batteries. A thermal route is established to synthesise CuNi alloys by using waste PCB, simultaneously as a Cu source and reducing agent from C-bearing polymer and waste NiMH batteries as Ni source. Thermal transformation and reduction studies were carried out at 1500 °C under an inert atmosphere. Initial characterization of raw materials was conducted in detail using various analytical techniques. Synthesised CuNi alloys were confirmed with ICP, EDS and XRD analyses. Material ratios of 75–25 wt% and 50-50 wt% of NiMH battery and PCB waste was considered and these range of compositions of e-waste, as raw materials, minimised the slag generation and optimised Ni recovery. Concentration of Nickel in the synthesised alloys was 20–30 wt%. Reduction extent of nickel oxide using PCB as reductant was confirmed by off-gas analysis. This approach has the potential to be implemented in selective synthesis of CuNi alloys instead of using conventional ores/reductant, to achieve target composition of alloys as per application requirements including marine/automotive/electronic industries. This novel approach promises significant benefits to divert e-wastes from landfill and provide sustainable solution for future metal alloy security. Highlights: Novel and sustainable pathway to synthesise CuNi alloys using e-waste. Waste PCB as Cu source and as reductant is used to reduce NiO from NiMH battery. Synthesised CuNi alloys are confirmed by XRD, EDS and ICP analysis. Ni is homogenously distributed in the alloy and complete recovery of Ni is achieved. The approach will divert huge volume of e-waste from landfill.